Ultrafast Surface-Specific Spectroscopy of Water at a Photoexcited TiO2 Model Water-Splitting Photocatalyst - Backus, Ellen H.G.; Hosseinpour, Saman; Ramanan, Charusheela; Sun, Shumei; Schlegel, Simon J.; Zelenka, Moritz; Jia, Xiaoyu; Gebhard, Maximilian; Devi, Anjana; Wang, Hai I.; Bonn, Mischa (Angewandte Chemie International Edition, 2024)
A critical step in photocatalytic water dissociation is the hole-mediated oxidation reaction. Molecular-level insights into the mechanism of this complex reaction under realistic conditions with high temporal resolution are highly desirable. Here, we use femtosecond time-resolved, surface-specific vibrational sum frequency generation spectroscopy to study the photo-induced reaction directly at the interface of the photocatalyst TiO2 in contact with liquid water at room temperature. Thanks to the inherent surface specificity of the spectroscopic method, we can follow the reaction of solely the interfacial water molecules directly at the interface at timescales on which the reaction takes place. Following the generation of holes at the surface immediately after photoexcitation of the catalyst with UV light, water dissociation occurs on a sub-20 ps timescale. The reaction mechanism is similar at pH 3 and 11. In both cases, we observe the conversion of H2O into Ti−OH groups and the deprotonation of pre-existing Ti−OH groups. This study provides unique experimental insights into the early steps of the photo-induced dissociation processes at the photocatalyst-water interface, relevant to the design of improved photocatalysts.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Interface; Photocatalyst; Sum Frequency Generation; Time-Resolved Spectroscopy; Titanium Dioxide